Foreign Direct Investment and Export Upgrading - Harding, Torfinn; Javorcik, Beata S. (The Review of Economics and Statistics, 2012)
This study presents evidence suggesting that attracting foreign direct investment (FDI) offers potential for raising the quality of exports in developing countries. Our analysis relates unit values of exports at the four-digit SITC level to data on sectors treated by investment promotion agencies as a priority in their efforts to attract FDI. The sample covers 105 countries from 1984 to 2000. The findings are consistent with a positive effect of FDI on unit values of exports in developing countries. The evidence for high-income economies is ambiguous. There is no indication that FDI increases the similarity of export structure of developing and developed economies.